2021
DOI: 10.1115/1.4050968
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of a Radial Flow Turbine Operates Under Various Pulsating Flow Shapes and Amplitudes

Abstract: Radial flow turbines are extensively used in turbocharging technology due to their unique capability of handling a wide range of exhaust gas flow. The pulsating flow nature of the internal combustion engine exhaust gases causes unsteady operation of the turbine stage. This paper presents the impact of the pulsating flow of various characteristics on the performance of a radial flow turbine. A three-dimensional computational fluid dynamic model was coupled with a one-dimensional engine model to study the realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Despite that, internal combustion engine exhaust gases have a pulsating flow nature which causes unsteady behavior of the turbine stage. Rezk et al (2021) presented the realistic effects of the pulsating flow of different characteristics on the performance of a radial turbine by coupling a 3-D CFD model with a 1-D engine model. Also, Mosca et al (2021) used unsteady CFD to study the effects of the parameterized characteristics of the mass flow pulse.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, internal combustion engine exhaust gases have a pulsating flow nature which causes unsteady behavior of the turbine stage. Rezk et al (2021) presented the realistic effects of the pulsating flow of different characteristics on the performance of a radial turbine by coupling a 3-D CFD model with a 1-D engine model. Also, Mosca et al (2021) used unsteady CFD to study the effects of the parameterized characteristics of the mass flow pulse.…”
Section: Introductionmentioning
confidence: 99%
“…This is motivated by the fact that the higher is the amplitude, the larger is the amount of mass flow which is found at a condition far from the cycle-averaged steady condition. Recently, Lee et al [21] and Rezk et al [22] investigated the effects of different pulse shapes on the turbine performance. In these numerical studies, the square profile was shown to have the largest detrimental effect on the turbine efficiency compared to realistic, sinusoidal, and triangular profiles.…”
Section: Introductionmentioning
confidence: 99%
“…This is motivated by the fact that the higher is the amplitude, the larger is the amount of mass flow which is found at a condition far from the cycle-averaged steady one. Recently, Lee et al [20] and Rezk et al [21] investigated the effects of different pulse shapes on turbine performance. The square profile was found to have the largest detrimental effect on the turbine efficiency compared to realistic, sinusoidal, and triangular profiles.…”
Section: Introductionmentioning
confidence: 99%